miR-21 and cathepsin B in familial Mediterranean fever: novel findings regarding their impact on disease severity - Emrah Yucesan; Mehmet Yildiz; Ramila Hajiyeva (BMJ Paediatrics Open)
Objective The limited predictive effect of genotype on familial Mediterranean fever (FMF) phenotype suggests that epigenetic factors and alternative mechanisms that may cause IL-1β release could contribute to phenotypic heterogeneity. The objective of this study was to examine the role of IL-1β levels and miR-21-5p, cathepsin B and pyrin levels, which were identified as potential factors causing IL-1β release through the use of bioinformatics tools, in the pathogenesis of FMF and their relationship with disease severity.Materials and methods 50 paediatric patients with FMF and 40 healthy children were enrolled in this study. Patients were divided into subgroups according to Pras disease severity score. Serum miR-21-5p expression levels were assessed by qRT-PCR, while serum pyrin, IL-1β and cathepsin B levels were determined by ELISA.Results Serum miR-21-5p was significantly downregulated in FMF patients compared with the control group (p<0.001), while serum pyrin, IL-1β and cathepsin B levels were markedly elevated (p<0.001 for each). Only miR-21-5p was negatively correlated with IL-1β (r=−0.855; p<0.001). In moderately severe FMF patients, miR-21-5p exhibited a statistically significant downregulation (p<0.001), whereas IL-1β and cathepsin B showed a statistically significant increase (p<0.001 and p<0.05, respectively). Furthermore, the Pras score showed a strong negative correlation (r=−0.738; p<0.001) with miR-21-5p levels. Multivariate logistic regression showed that in FMF, a one-unit decrease in miR-21 increased disease severity risk 6.76-fold, while a one-unit increase in cathepsin B raised it 1.71-fold.Conclusion This might be considered one of the mechanisms for subclinical inflammation in paediatric FMF patients through increased activation of cytokines via the downregulation of miR-21-5p. Our findings suggest that miR-21-5p and IL-1β play key roles in subclinical inflammation, and these molecules might be a potential therapeutic target.